ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA MENGGUNAKAN METODE JUMPING TASK PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Putri, Chika Ramadhanty Twine Ayu; Hobri, H; Fatahillah, Arif (Kadikma, 2018)
This study describes the level of student problem solving based on NCTM SMPN 7 Jember students in solving SPLDV problems using the jumping task method. Data collection methodswhich used are tests and interview. The subjects studied further in this study were 3 students, one student was included in the level of “very good” problem solving, one student falls under the category of “good” at problem solving, and the other one belongs to the category of “moderate”. The results showed that 7 people were included in the very good category, 18 people were in the good category, 13 people were in the category of “moderate” and no one was in the category of “poor”. Keywords: problem solving, NCTM, jumping task